The lost world of the prophets: Old Testament prophecy and apocalyptic literature in ancient context - Walton, John H. (Lost world series, 2024)
"Are the prophets speaking about their own times, about our present, or about some still-unrealized future? Applying his signature method, John Walton provides a clear, helpful guide to the nature of biblical prophecy and apocalyptic literature that will help us avoid potential misuse and reclaim the message of the prophets for our lives"--